2019
DOI: 10.1093/ibd/izy364
|View full text |Cite
|
Sign up to set email alerts
|

A JAK1 Selective Kinase Inhibitor and Tofacitinib Affect Macrophage Activation and Function

Abstract: Background Janus kinases (JAKs) mediate cytokine signaling involved in inflammatory bowel disease. The pan-JAK inhibitor tofacitinib has shown efficacy in the treatment of ulcerative colitis. However, concerns regarding adverse events due to their wide spectrum inhibition fueled efforts to develop selective JAK inhibitors. Given the crucial role of myeloid cells in intestinal immune homeostasis, we evaluated the effect of pan-JAK and selective JAK inhibitors on pro- and anti-inflammatory macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
46
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 53 publications
8
46
1
Order By: Relevance
“…In agreement with this observation, in vitro experiments and in vivo animal models revealed that tofacitinib up-regulated ABCA1 expression, promoted anti-inflammatory macrophage polarization, improved EC function, and attenuated atherosclerosis (Table 1 and Fig. 3;De Vries et al, 2019;Furumoto et al, 2017;Pérez-Baos et al, 2017;Wang et al, 2017). However, recently the Oral Surveillance study revealed a statistically significant and clinically relevant increase in pulmonary embolism and an increased mortality in patients older than 50 yr with an increased CV risk when treated with a tofacitinib dose of 10 mg twice daily ( Fig.…”
Section: Anti-ifn/ifnar Signaling Therapiessupporting
confidence: 79%
“…In agreement with this observation, in vitro experiments and in vivo animal models revealed that tofacitinib up-regulated ABCA1 expression, promoted anti-inflammatory macrophage polarization, improved EC function, and attenuated atherosclerosis (Table 1 and Fig. 3;De Vries et al, 2019;Furumoto et al, 2017;Pérez-Baos et al, 2017;Wang et al, 2017). However, recently the Oral Surveillance study revealed a statistically significant and clinically relevant increase in pulmonary embolism and an increased mortality in patients older than 50 yr with an increased CV risk when treated with a tofacitinib dose of 10 mg twice daily ( Fig.…”
Section: Anti-ifn/ifnar Signaling Therapiessupporting
confidence: 79%
“…In patients who demonstrate a clinical response to infliximab, a distinct subset of macrophages expressing CD206 is induced and expanded compared with patients who failed to respond to the biologic (79). Furthermore, tofacitinib, a small molecule JAK inhibitor developed for the treatment of IBD as well as other immune-mediated disorders, affects macrophage polarization and function (80,81). Upon treatment with tofacitinib, both murine and human macrophages increase transcription of alternatively activated macrophage markers and increase levels of IL-10 secretion while inhibiting IFN-g signaling, which may help ameliorate weight loss and disease activity and further highlight its therapeutic potential (81).…”
Section: Alterations To Macrophage Function During Resolution Of Inflmentioning
confidence: 99%
“…Furthermore, tofacitinib, a small molecule JAK inhibitor developed for the treatment of IBD as well as other immune-mediated disorders, affects macrophage polarization and function (80,81). Upon treatment with tofacitinib, both murine and human macrophages increase transcription of alternatively activated macrophage markers and increase levels of IL-10 secretion while inhibiting IFN-g signaling, which may help ameliorate weight loss and disease activity and further highlight its therapeutic potential (81). Hence, there is some indirect evidence that macrophage activation pathways associated with tissue repair and type 2 cytokine responses could be associated with mucosal healing in IBD patients or with the activity of successful therapeutic agents used to treat IBD patients.…”
Section: Alterations To Macrophage Function During Resolution Of Inflmentioning
confidence: 99%
“…Tofacitibib inhibits the effect of IL-6, IL-10, IFN-γ, INF-α and granulocyte macrophage-colony stimulating factor (GM-CSF), thus suppressing neutrophils NOD-like receptor family pyrin domain-containing 3 (NLRP3) activation and IL-1β production 9. Tofacitinib also suppresses macrophage activation and function 10. It provides some experimental evidence to use tofacitinib in refractory AOSD.…”
mentioning
confidence: 99%